2019
DOI: 10.3390/cancers11111781
|View full text |Cite
|
Sign up to set email alerts
|

Radiation and Stemness Phenotype May Influence Individual Breast Cancer Outcomes: The Crucial Role of MMPs and Microenvironment

Abstract: Breast cancer is the most common cancer in women. Radiotherapy (RT) is one of the mainstay treatments for cancer but in some cases is not effective. Cancer stem cells (CSCs) within the tumor can be responsible for recurrence and metastasis after RT. Matrix metalloproteases (MMPs), regulated mainly by tissue inhibitors of metalloproteinases (TIMPs) and histone deacetylases (HDACs), may also contribute to tumor development by modifying its activity after RT. The aim of this work was to study the effects of RT on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 79 publications
1
14
0
Order By: Relevance
“…However, chemotherapy is not the only treatment that can alter the tumor secretome. As shown in a previous study by our research team, the dose of radiation therapy administered in vitro and in vivo affects the expression of several MMPs and their inhibitors [237]. These alterations were related with the molecular profile of breast cancer.…”
Section: Secretome In Chemoresistancesupporting
confidence: 56%
See 1 more Smart Citation
“…However, chemotherapy is not the only treatment that can alter the tumor secretome. As shown in a previous study by our research team, the dose of radiation therapy administered in vitro and in vivo affects the expression of several MMPs and their inhibitors [237]. These alterations were related with the molecular profile of breast cancer.…”
Section: Secretome In Chemoresistancesupporting
confidence: 56%
“…These alterations were related with the molecular profile of breast cancer. The study not only highlights the fundamental role played by the specific characteristics of each tumor and TME in response to treatment, but also that radiotherapy promotes the secretion of matrix remodeling enzymes involved in the dispersion, invasiveness and metastasis of CSCs and in the EMT process [237]. Additionally, Shen et al demonstrated that chemotherapy induces breast cancer cells to secrete exosome-derived miR-9, miR-195 and miR-203a, which induces CSC phenotypes and expression of stemness-associated genes, thus generating cancer cell communication and self-adaptation to survive treatment [39].…”
Section: Secretome In Chemoresistancementioning
confidence: 96%
“…CSCs are a small portion of cells within tumors and important research targets because of their tumorigenic potential and stemness properties [ 96 , 97 ]. CSCs are found mainly in hypoxic niches, with low pH and with less nutrients [ 75 , 98 ], where they can initiate, maintain, and disseminate tumors [ 64 , 96 ]. CSCs are also involved tumor recurrence and metastasis due to their radio- and chemoresistance ability [ 96 , 99 ].…”
Section: Cscs and Microenvironmentmentioning
confidence: 99%
“…CSCs are found mainly in hypoxic niches, with low pH and with less nutrients [ 75 , 98 ], where they can initiate, maintain, and disseminate tumors [ 64 , 96 ]. CSCs are also involved tumor recurrence and metastasis due to their radio- and chemoresistance ability [ 96 , 99 ]. This resistance ability is a consequence of their recovery capacity conferred by intrinsic properties of the cells themselves and extrinsic properties from the TME [ 64 ].…”
Section: Cscs and Microenvironmentmentioning
confidence: 99%
See 1 more Smart Citation